ANALYSIS OF APPLICATION OF ACCOUNTING INFORMATION SYSTEM IN PROCESSING SALES TRANSACTION AT PT. DAIHATSU ASTRA MOTOR SISINGAMANGARAJA - Budiman Rosyadi Nasution (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2022)
This study aims to examine the sales accounting information system implemented by PT Daihatsu Astra Motor Sisingamangaraja. Then it can be identified whether the information system has been implemented according to the right internal control structure or not and to determine the company's development through financial ratios that are limited to the sales department. This type of research is a case study, which contains exposure or relevant data from the results of research on the object. Qualitative methods are used in flowchart analysis and quantitative methods are used to calculate financial ratios that are limited to sales. Primary data is data that comes from the original source and is collected specifically for the purposes of the research being conducted. Secondary data is data produced by companies such as financial statements and accounting records. Data collection methods are interviews and direct observation. The results of this study are overall PT Daihatsu Astra Motor Sisingamangaraja has carried out car sales activities, spare parts / spare parts and service services with an accounting information system in accordance with the components of the internal control structure model. The majority of transactions that occurred at PT Daihatsu Astra Motor Sisingamangaraja actually decreased, this was due to the author's limitations in obtaining related financial statement information. Thus, it can be concluded that the accounting information system applied by the company is mostly appropriate and effective because it is appropriate so that it can support internal sales control.